Analysis for anodized film blackening of aluminum alloy components. Issue 3 (April 2021) - Zou, Xiaohui; Jiang, Chengjun; Lv, Chaojun; Sun, Xiaojiao; Luo, Jing; Chen, Shumao
Abstract: Sulfuric acid anodic oxidation is an important means to improve the corrosion resistance of aluminum alloy components. The blackening phenomenon of aluminum alloy components after sulfuric acid anodizing is analyzed by chemical composition test, mechanical property test, process parameters analysis, metallographic examination and other tests. The analysis results are compared with normal color components after anodized. The result shows that the unsufficient solid solution heat treatment is the main reason for anodized film blackening of the aluminum alloy components, which result in the abnormal microstructures. At last, the measure of secondary heat treatment is taken to solve this problem effectively.